Menegakkan Jurnalisme Etis dalam Pemberitaan Kasus Terorisme - Salvatore Simarmata (Jurnal InterAct, 2013)
Media coverage of terrorism has tendency of bias because both media and terrorists take advantages in the relationship. Media benefit much from the news value of the striking acts of terror that spark fear and anger at the same time. The terrorists win free publication of their actions in achieving their goals. Therefore the credibility of the news media should be built upon the ethical journalism practice to eliminate the bias. This article proposed a theoretical and practical foundation for implementing ethical journalism in covering terrorism. Journalists should comply with a new principle of objectivity in reporting terrorism. As the society needs accurate information about events around them, news media should be able to provide ―first  aid‖  package of information, so that members of the society can act rationally and be calm during the tense situation. Ethical journalism with a renewed standard of objectivity could keep the first aid of information constantly flowing to the society facing fear and danger of terrorism.